The effect of uterine-derived mesenchymal stromal cells for the treatment of canine atopic dermatitis: A pilot study - Black, Linda; Zacharias, Shelly; Hughes, Mark; Bautista, Rachel; Taechangam, Nopmanee; Sand, Theodore (Frontiers in Veterinary Science, 2022)
Canine atopic dermatitis (cAD) is a common allergic skin condition among dogs that may respond to treatment with mesenchymal stromal cells (MSCs). The aim of this pilot study was to evaluate the safety and efficacy of allogeneic uterine tissue-derived MSCs (UMSCs) for the reduction and control of clinical signs associated with cAD. At two sites, seven client-owned dogs with cAD received two doses of approximately 3.6 x 107 UMSCs given intravenously over 30 minutes, on Day 0 and Day 14, with monthly clinical follow-up until Day 90 and optional owner phone interview on Day 180. Primary outcomes were pruritus and skin lesions. Pruritus was measured by the owner-assessed Pruritus Visual Analog Scale (PVAS), with treatment success defined as a 2-point reduction in PVAS score at any timepoint after treatment. Skin lesions were evaluated by two veterinarians according to the Canine Atopic Dermatitis Extent and Severity Index (CADESI-4). The secondary outcome was safety, which was evaluated via physical exam and hematology, including complete blood count (CBC), serum chemistry, and urinalysis (UA). Treatment was generally well tolerated and associated with a significant reduction in PVAS on Day 30 that was maintained through Day 180. On Day 60, five dogs (71%) achieved treatment success (at least 2-point reduction in PVAS), and three dogs (43%) had a PVAS improvement of 4-5 points. Mean CADESI-4 score was significantly improved on Day 14, Day 30, Day 60, and Day 90, with the lowest mean score observed on Day 60. Three dogs exhibited mild and transient adverse events. These findings suggest that IV-administered allogeneic UMSCs reduce and control clinical signs of cAD, with a durable benefit lasting 3-6 months.